A MODELAGEM MATEMÁTICA E SUAS IMPLICAÇÕES PARA O DESENVOLVIMENTO DA CRIATIVIDADE - Pereira, Emanueli (2008)
The discussions around the criativity in the schoolar scope and particularly the interest in studying the criativity into Mathematical Modeling tasks encouraged the elaboration of the present investigation. Therefore, this research focused on the study of the criativity into Mathematical Modeling applications inside classroom. The question around research is: Do the tasks developed through Mathematical Modeling in the perspective Maths Education adopted favor the criativity’s development? In function of main question and other around this investigation, the following aims get presents: identify and analise aspects relating to the criativity present in tasks made use in Mathematical Modeling as a learning methodology and investigation described in some papers developed in Brazilian universities Post-Graduation Programs, and produce indicators about Mathematical Modeling relation and Criativity. The present research was developed into a qualitative approach through the analysis of academics researches (papers) advised by Barbosa, Burak, and Caldeira, writers that according to Klüber (2007), are harmonyzed in many aspects in relation to Mathematical Modeling, that take part beyond Mathematics itself and other knowledge areas. It characterizes as a bibliographic or documental study with an outline from meta analytic research. According to Fiorentini and Lorenzato (2006) it constitutes a sistematic review from other researches that carries out a critic evalluation and produces new results or synthesis up to these studies confront beyond those scored. Through the sense to approach the criativity in its various aspects, it was identified in the selected papers descriptions describers from literature that drawn how factors refer to the criativity. On the final of the investigation it was pointed out how the results as the student’s freedom of action and the task in the heuristic perspective beyond other, are fundamentals in order to possibility the criativity development inside classroom in a Mathematical Modeling task. These aspects depend on great part of attitude adopted by the teacher during the task. Furthermore, the Mathematical Modeling in approaching situations from student’s reality may arouse major interest by Mathematics and as a concequence supplying the abilities development related to the criativity in Mathematics.